A computational model for dynamic strain localization in unsaturated elasto‐viscoplastic soils - Oka, Fusao; Shahbodagh, Babak; Kimoto, Sayuri (International Journal for Numerical and Analytical Methods in Geomechanics, 2019)
Summary Strain localization has been the subject of extensive theoretical and numerical studies over the last four decades. The static and dynamic strain localization in both dry and water‐saturated geomaterials has widely been investigated numerically. However, studies on unsaturated geomaterials have been insufficient. This paper presents a computational model for nonlinear dynamic analysis of strain localization in multiphase geomaterials. The discretization of the governing equations is achieved using the finite element method in the finite deformation regime with the updated Lagrangian description. An elasto‐viscoplastic model extended to include the effect of suction on the behavior of partially saturated clay is used in the formulation. The nonlinear kinematic hardening rule and softening due to the structural degradation of soil particles are taken into account in the model. The inception and progression of localization in fully saturated and unsaturated clay under dynamic compressive loading are investigated. In the unsaturated case, the strain localization becomes more pronounced and much clearer shear bands are formed. More brittleness is observed in the unsaturated case due to the collapse of suction force caused by shearing. This demonstrates that even though suction improves the mechanical properties of soil, ie, increasing the stiffness and shear strength, the hypothesis of fully saturation is not at all on the side of safety due to the drastic loss of strength associated with the collapse of suction which may cause a strong strain localization.